Influence of servant leadership on job satisfaction : a study ofland and survey department / Kuldip Singh - Singh, Kuldip (UiTM Cawangan Johor, 2019)
Servant leadership has been found to bring positive benefits to an organization and its employees. This study examines the influence of servant leadership on job satisfaction in the Land and Survey Department (LSD). In this study, the structured questionnaire survey was carried out. Eighty two (82) questionnaires collected and were analyzed accordingly to test the various hypotheses. The measurement items were rated with 5-point Likert. Goodness of measures were performed with SPP software and all items measured were found to be reliable and valid. The results indicate that servant leadership is positively correlated with job satisfaction. In addition, all dimensions of service leadership are also significantly correlated with job satisfaction. The study also found no significance difference in job satisfaction based on demographic factors. These results imply that servant leadership in the public sectors is highly correlated with job satisfaction and that demographic factors do not make a difference in the level of job satisfaction in the selected organization. This study provides insights on the relationship between servant leadership and job satisfaction in the public sector. The findings of this study may help public sector to better understand servant leadership and its effect on job satisfaction.